The Demand for Loans : Governments Restructure Their Debt - Harford, Tim (World Bank, Washington, DC, 2012)
More than ever, governments in developing countries have access to capital markets, but most are not using it. Instead, they have restructured their debt portfolios, cutting the share of private sector debt and increasing the share of longer-term multilateral debt. While some argue that this increase in official debt is alarming, the evidence suggests that most governments are sensibly taking advantage of their menu of financing options extending maturities to lessen their vulnerability to the rollover risk posed by shorterterm debt and reducing their overall debt ratios.